2016
DOI: 10.1159/000443987
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Prenatal Dexamethasone on the Rat Pituitary Gland and Gonadotropic Cells in Female Offspring

Abstract: Glucocorticoids have a strong influence on growth and maturation of fetal organ systems, but overexposure to exogenous glucocorticoids may retard fetal growth and alter developmental processes in sensitive tissues. The aim of this study was to specifically determine whether prenatal exposure to dexamethasone (Dx) altered normal development and function of pituitary gonadotropic cells in neonatal, infant and peripubertal female offspring. On day 16 of pregnancy, rat dams received 1.0 mg Dx/kg body weight (BW) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Dexamethasone inhibits serum luteinising hormone (LH) (Ristić et al, 2016) and testosterone (Sadeghzadeh, Mehranjani, & Mahmoodi, 2019), which affect the testicular endocrine function; therefore, it affects sperm transportation, sperm metabolism and sperm maturation in the epididymis (Tsantarliotou et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Dexamethasone inhibits serum luteinising hormone (LH) (Ristić et al, 2016) and testosterone (Sadeghzadeh, Mehranjani, & Mahmoodi, 2019), which affect the testicular endocrine function; therefore, it affects sperm transportation, sperm metabolism and sperm maturation in the epididymis (Tsantarliotou et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…These data document the programming effect of Dx at the level of the ovary. Clear programming effects of Dx were also detected in the hypothalamus and pituitary gland . Dx‐induced changes at all three levels of the hypothalamo–pituitary–gonadal axis may contribute seriously to impaired reproductive function during adulthood.…”
Section: Discussionmentioning
confidence: 97%
“…Expression of proliferating cell nuclear antigen (PCNA) and caspase‐3 in the fetal ovaries was investigated using immunohistochemical methods . After deparaffinization and rehydratation, two‐micrometer‐thick serial sections were pretreated with citrate buffer for antigen retrieval according to standard protocols.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, few studies have assessed circulating sex steroids in female offspring following developmental overexposure to GCs. One study showed that maternal stress in guinea pigs increased T levels in female offspring during adulthood [ 212 ], whereas prenatal DEX led to reduced circulating follicle-stimulating hormone and luteinizing hormone in peripubertal rats [ 213 ] and lower serum E2 in adult female offspring [ 214 ]. The most consistent results reported in female offspring were alterations in the onset of puberty and variations in the length of estrus stages [ 215-220 ] as well as decreased numbers of healthy primordial follicles [ 221 , 222 ], likely due to the proapoptotic action of DEX reported on human and rat fetal ovaries [ 223 , 224 ].…”
Section: Evidence For Developmental Sex-steroid Disruption By Abermentioning
confidence: 99%